Growth of 2H stacked WSe2 bilayers on sapphire. Issue 6 (26th July 2019) - Han, Ali; Aljarb, Areej; Liu, Sheng; Li, Peng; Ma, Chun; Xue, Fei; Lopatin, Sergei; Yang, Chih-Wen; Huang, Jing-Kai; Wan, Yi; Zhang, Xixiang; Xiong, Qihua; et al.
Abstract : Bilayer WSe2 nuclei were initially grown along the atomic steps of a sapphire substrate, resembling a "graphoepitaxial mechanism" and gradually formed into overlapped 2H stacked WSe2 bilayers. Abstract : Bilayers of two-dimensional (2D) transition metal chalcogenides (TMDs) such as WSe2 have been attracting increasing attention owing to the intriguing properties involved in the different stacking configurations. The growth of bilayer WSe2 by chemical vapor deposition (CVD) has been facilely obtained without proper control of the stacking configuration. Herein, we report the controlled growth of bilayer WSe2 crystals as large as 30 μm on c -plane sapphire by the CVD method. Combining second harmonic generation (SHG), low-frequency Raman and scanning transmission electron microscopy (STEM), we elucidate the as-grown bilayer WSe2 with a 2H stacking configuration. Atomic force microscope (AFM) measurements reveal that the prominent atomic steps provide the energetically favorable templates to guide the upper layer nuclei formation, resembling the "graphoepitaxial effect" and facilitating the second WSe2 layer following the layer-by-layer growth mode to complete the bilayer growth. Field-effect charge transport measurement performed on bilayer WSe2 yields a hole mobility of up to 40 cm 2 V −1 s −1, more than 3× higher than the value achieved in monolayer WSe2 -based devices. Our study provides key insights into the growth mechanism of bilayer WSe2 crystals on sapphire and unlocks the opportunity for potential bilayer and multilayer TMD electronic applications.